MACROCHELID MITES FROM A NEST OF HONEY BEE APIS DORSATA DORSATA AT BOGOR BOTANICAL GARDEN, WEST JAVA, INDONESIA - Sri Hartini; Sih Kahono; Gen Takaku (TREUBIA, 2013)
Thirteen species of macrochelid mites belonging to the genera Holostaspella, Macrocheles, Neopodocinum and Glyptholaspis were collected from a nest of honey bee Apis dorsata dorsata at Bogor Botanical Garden, Bogor, West Java, Indonesia. Of these, one species was described as new to science, two species were recorded from Indonesia for the first time, and all species were recorded from nest of Apis dorsata dorsata for the first time. Macrocheles nidus sp. nov. is similar to some species of scutatus subgroup, but it is discernible from the latter by the pilosity of dorsal setae.